Improving English Writing Achievement Using Game-Based Learning at the 11th Grade Students at Islamic Senior High School - Aulia Rachman Ashari; M. Yahya Ashari; Dwi Fita Heriyawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This classroom action research aims to improve 11th-grade students’ writing achievement through the application of game-based learning (GBL). The research was conducted at Madrasah Aliyah Negeri 2 Jombang from February to March 2025 and was implemented in one cycle consisting of six meetings. Before the intervention, only 65% of students reached the “Good” to “Excellent” categories in writing analytical exposition texts. The acting activities were carried out across six meetings. In the first meeting, students used Quizizz to practice writing exposition texts. The second meeting introduced vocabulary practice through Gimkit. In the third meeting, students collaboratively learned to write exposition texts and practiced vocabulary by filling in blanks in Gimkit, with the teacher guiding the process. The fourth meeting focused on building understanding among classmates through talk-to-talk activities, concluded by the researcher’s reflections. The fifth meeting was an individual writing assessment to measure students’ analytical exposition writing skills. The sixth meeting used the game-based Uno Flip activity to observe students’ engagement. The findings show an improvement in writing performance after implementing game-based learning: 6 students (20%) reached the “Excellent” category, 18 students (60%) were in “Good,” 4 students (13.3%) were in “Fair,” and only 2 students (6.7%) remained in “Poor.” Overall, 80% of students achieved “Good” to “Excellent,” an increase from the 65% baseline. However, this study is limited by its single-cycle design and focus on one text genre. In conclusion, game-based learning has proven effective in improving writing performance and offers a fun, creative, and student-centered approach to English learning.